Lipid Droplets Protect Aging Mitochondria and Thus Promote Lifespan in Yeast Cells - Kovacs, Melanie; Geltinger, Florian; Verwanger, Thomas; Weiss, Richard; Richter, Klaus; Rinnerthaler, Mark (Frontiers in Cell and Developmental Biology, 2021)
Besides their role as a storage for neutral lipids and sterols, there is increasing evidence that lipid droplets (LDs) are deeply involved in cellular detoxification. LDs are in close contact to a broad variety of organelles where protein- and lipid exchange is mediated. Mitochondria as a main driver of the aging process produce reactive oxygen species (ROS) originating from a premature leakage of the respiratory chain. These reactive molecules propagate the oxidation of proteins as well as lipids, which play an essential role in inducing autophagy and apoptosis. LDs as highly dynamic organelles mediate a potent detoxification mechanism by taking up toxic lipids and proteins. A stimulation of a certain subset of LDs induced by the simultaneously overexpression of Lro1p and Dga1p (both encoding acyltransferases) prolongs the chronological as well as the replicative lifespan of yeast cells. The increased number of LDs clearly improve certain mitochondrial parameters such as morphology and ROS production.